Qualitative research in psychology : expanding perspectives in methodology and design - Camic, Paul Marc, 1955- (2021)
"Qualitative methods of research contribute valuable information to our understanding and expanding knowledge of psychological phenomena. This updated edition of Qualitative Research in Psychology builds upon the groundwork laid by its acclaimed predecessor, bringing together a diverse group of scholars to illuminate the value that qualitative methods bring to studying psychological phenomena in depth and in context. A range of techniques, guiding paradigms, and rich case examples are explored, demonstrating qualitative methodologies as alternative and complementary to quantitative methods, as a means of exploration and theory building, and as a means of developing and evaluating complex behavior-change interventions. Thoroughly updated chapters reflect advances in this dynamic field. New authors and chapters describe emerging methodologies, qualitative meta-analysis, and how qualitative methods can contribute to a wider psychological approach to research. Pragmatic issues, such as how to choose a method or combination of methods to suit the research question and study design, how to determine the ideal sample size, and how to balance journal space limitations with the need for transparency in describing the study, will be valuable to all readers"--
"This updated edition builds upon the groundwork laid by its acclaimed predecessor, bringing together a diverse group of scholars to illuminate the value that qualitative methods bring to studying psychological phenomena in depth and in context. A range of techniques, guiding paradigms, and rich case examples are explored, demonstrating qualitative methodologies as alternative and complementary to quantitative methods, as a means of exploration and theory building, and as a means of developing and evaluating complex behavior-change interventions"--
Machine generated contents note: Preface to the Second Edition -- Paul M. Camic -- -- Part 1. Laying the Foundations: The Pluralistic Approaches of Qualitative Inquiry -- -- Chapter 1. Going Around the Bend and Back: Qualitative Inquiry in Psychological Research -- Paul M. Camic -- -- Chapter 2. Choosing a Qualitative Method: A Pragmatic, Pluralist Perspective -- Chris Barker and Nancy Pistrang -- -- Chapter 3. Narrative in Qualitative Psychology: Approaches and Methodological Consequences -- Michael Bamberg -- -- Chapter 4. Information Power and Sample Size in Qualitative Studies -- Kirsti Malterud, Volkert Siersma, and Ann Dorrit Guassora -- -- Part 2. Methodologies for Qualitative Researchers: Helping to Understand the World Around Us -- -- Chapter 5. Participation, Power and Solidarities Behind Bars: A 25-Year Reflection on Critical Participatory Action Research on College in Prison -- Michelle Fine, Maria Elena Torre, Kathy Boudin, and Cheryl Wilkins -- -- Chapter 6. Narrative Data and Narrative Analysis -- Michael Murray -- -- Chapter 7. Discursive Psychology: Capturing the Psychological World as it Unfolds -- Jonathan Potter -- -- Chapter 8. Interpretative Phenomenological Analysis -- Jonathan A. Smith and Megumi Fieldsend -- -- Chapter 9. Situational Analysis: Mapping Relationalities in Psychology -- Rachel Washburn, Adele Clarke, and Carrie Friese -- -- Chapter 10. What Lies Beneath? Eliciting Grounded Theory Through the Analysis of Video-Recorded Verbal and Nonverbal Interactions -- Colin Griffiths -- -- Chapter 11. Under Observation: Line Drawing as an Investigative Method in Focused Ethnography -- Andrew Causey -- Part 3. Developing and Expanding Qualitative Research -- -- Chapter 12. Into the Ordinary: Lessons Learned From a Mixed-Methods Study in the Homes of People Living With Dementia -- Emma Harding, Mary Pat Sullivan, Sebastian J. Crutch, and Keir Yong -- -- Chapter 13. Using Qualitative Research for Intervention Development and Evaluation -- Lucy Yardley, Kat Bradbury, and Leanne Morrison -- -- Chapter 14. Qualitative Meta-Analysis: Issues to Consider in Design and Review -- Kathleen M. Collins and Heidi M. Levitt -- .
Revised edition of Qualitative research in psychology, c2003.
Includes bibliographical references and index.
Keywords: Psychology -- Qualitative research; PSYCHOLOGY / Research & Methodology; PSYCHOLOGY / Assessment, Testing & Measurement